Factors influencing health information acquisition behavior from a social capital theory perspective: a study of Zhihu users - Jia, Juncheng; Bao, Zemenghong; Wang, Haochen; Cao, Yuqun; Yu, Luhan; Lv, Kun (Frontiers in Public Health, 2025)
The rapid development and widespread use of Internet technology have facilitated access to health information for the general public. However, the behavior of acquiring health information is influenced by multiple factors, resulting in differences and even inequalities. This paper aims to explore the influencing factors of user health information acquisition behavior, find feasible ways to optimize such behavior and maximize the utility of health information for users. By utilizing the Zhihu Q&A platform to obtain user health information and integrating social capital theory, the study identifies the influencing factors of user health information acquisition behavior. It utilizes fuzzy set qualitative comparative analysis to examine these factors as antecedent variables, with the dissemination heat of health information as the outcome variable. The study reveals that the structure, relationships, and cognitive dimensions of social capital significantly impact user health information acquisition behavior. The configuration path for user health information acquisition behavior generated by the fsQCA 3.0 software provides recommendations to maximize the utility of health information.